Zerumbone Attenuates the Severity of Acute Necrotizing Pancreatitis and Pancreatitis-Induced Hepatic Injury - Deng Wenhong; Yu Jia; Wang Weixing; Chen Xiaoyan; Chen Chen; Xu Sheng; Jin Hao (Mediators of Inflammation)
This paper investigated the potential effects of zerumbone pretreatment on an acute necrotizing pancreatitis rat model induced by sodium taurocholate. The pancreatitis injury was evaluated by serum AMY, sPLA2, and pancreatic pathological score. Pancreatitis-induced hepatic injury was measured by ALT, AST, and hepatic histopathology. The expression of I-κBα and NF-κB protein was evaluated by western blot and immunohistochemistry assay while ICAM-1 and IL-1β mRNA were examined by RT-PCR. The results showed that AMY, sPLA2, ALT, and AST levels and histopathological assay of pancreatic and hepatic tissues were significantly reduced following administration of zerumbone. Applying zerumbone also has been shown to inhibit NF-κB protein and downregulation of ICAM-1 and IL-1β mRNA. The present paper suggests that treatment of zerumbone on rat attenuates the severity of acute necrotizing pancreatitis and pancreatitis-induced hepatic injury, via inhibiting NF-κB activation and downregulating the expression of ICAM-1 and IL-1β.